Preparation and performance study of waterproof and breathable layer of alginate/aramid-based fabrics and flame-retardant multilayer combination - Xiaoxiao Chen; Min Li; Miao Yu; Yutian Li (Designed Monomers and Polymers)
Alginate fibers have excellent flame-retardant properties and make up for other material defects by blending. To investigate the influence of the blending ratio of alginate fibers on the flame-retardant properties of waterproof and breathable layers for firefighting suits, this paper utilizes the needle-punching and hot-pressing nonwoven reinforcement processes to prepare waterproof and breathable layers based on alginate/aramid base cloths and conducts a series of performance tests on them. The results show that the char residue content of alginate blended base cloth is significantly improved relative to pure aramid, and the addition of alginate fibers to the base cloth of the waterproof and breathable layer improves its flame retardancy and thermal stability. The overall performance of the alginate/aramid blended base fabric waterproof and breathable layer was better than that of the aramid-based waterproof and breathable layer. Moreover, in the flame-retardant multilayer fabric system for firefighting apparel, the multilayer fabric system containing the alginate/aramid-based waterproof and breathable layer showed higher thermal protection performance. Therefore, the alginate/aramid-based waterproof and breathable layer can enhance the overall flame-retardant performance of firefighting clothing to a certain extent.